PERLINDUNGAN HUKUM BAGI KONSUMEN PERUMAHAN ATAS PENYALAHGUNAAN FASILITAS SOSIAL DAN FASILITAS UMUM MENJADI LAHAN BISNIS - Abdullah Emile oemar Alamudy; Martin Roestamy; Endeh Suhartini (JURNAL ILMIAH LIVING LAW, 2022)
Social Facilities and Public Facilities are supporting facilities in a residential area to provide interaction and activities for the residents. This Social and Public facility has existed since a housing will be built which is stated in the Site Plan to be known by housing consumers. However, the site plans sometimes turn into business from their original functions. With the normative juridical research method, the author tries to examine laws and regulations relating to Social and Public Health by analyzing the handling of changes in these facilities that have changed functions into business land as legal protection for housing consumers and efforts to resolve the switching function of these facilities by developers as a legal liability. The results of the research carried out, that the change into a business area in a housing/settlement is very detrimental to the rights of customers to get their rights to the facilities.